Santo Agostinho - "de musica" - Amato, Rita de Cássia Fucci (Educação e Filosofia, 2008)
Abstract: The main idea of this dialogue is the ascension to the knowledge of God and His existence in the world. In the first five books, Agostinho takes an apparently technical approach to organize it. He also passes on technical knowledge about the rhythm, the metric and the verse, culminating in the sixth book with conception of God. The organization of this paper includes, on one hand, the ascension to God in the author’s view. On the other hand, it reflects the lack of unity in the Agostinian work, with admirable beauty and richness, establishing a harmonious link between the sensitive beauty, the Criator and Supreme Beauty. Keywords: Agostin; Aesthetics; Medieval Philosophy. Resumo: O pensamento central neste diálogo é a ascensão ao conhecimento de Deus e Sua presença no mundo. Agostinho elabora-o de forma aparentemente técnica, nos cinco primeiros livros, e transmite conhecimentos técnicos sobre o ritmo, o metro e o verso e culmina no sexto livro com a concepção de Deus. A organização do trabalho girou, por um lado, em torno da questão do autor – a ascenção a Deus; por outro lado, refletiu a ausência de unidade da obra agostiniana, numa riqueza e beleza admiráveis, estabelecendo uma harmoniosa ponte entre a beleza sensível e a Beleza Suprema e Criadora. Palavras-chave: Agostinho; Estética; Filosofia Medieval.